IMPLEMENTATION BLUE OCEAN STRATEGY (STRATEGI SAMUDRA BIRU) AT GROUP WINGS - Hermanto Hermanto (LPPM, 2011)
Applying of blue ocean strategy at group wings a group peripatetic big company in all area effort for retail especially at requirement products of household in general. Group wings stands up the year 1948 with location in Kota Surabaya, in implementing sale strategy of its (the product inculcating image and also motto that consumer considering of product yielded by company group this wings. Peripatetic wings products in the field of majoring basic necessities which is easy got where just is of all [by] Indonesia region with the price of reachd, product with quality, design, feature (the facility and usefulness), brand-name, packaging, measure, service, warranty and replacement if happened damage. Including one of blue ocean strategy done by group wings is price what covers price list elements, cutting, bonus, duration of payment, credit order. Sales promotion, advertising, sales force, public relations direct marketing, all the things has covered a strategy doing no emultion in red ocean. Wht causes indisposed emultion and red blood generating retrogression of effort for the industry. In the case of special of company group wings which I do research has far from red Ocean and executes Blue Ocean strategy. Keywords: Blue ocean strategy, Produk-produk Rumah Tangga, Kesehatan dan Makanan.